The Role of Private Sector Annuities Markets in an Individual Accounts Reform of a Public Pension Plan - Mackenzie, George (IMF Working Papers; Working Paper, 2002)
Pension reforms that establish individual accounts will diminish the relative importance of the traditional state pension while creating a significant role for individual accounts in providing income for retirement. This paper surveys the policy issues this new role entails. It offers general advice to countries considering such issues as the restrictions to be placed on the timing, extent, and form of withdrawals from individual accounts and the need for mandatory annuitization (conversion into annuities) of accumulated account balances. The paper also considers the role that private annuity markets should play and related regulatory, social safety net, tax, and administrative questions.